PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KONDISI FINANCIAL DISTRESS TERHADAP LUAS PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN PERUSAHAAN - Godeliva Poluan; Paskah Ika Nugroho (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
This study examines the mechanism of corporate governance and financial distress conditions on the voluntary disclosure in the annual report. Elements of mechanism corporate governance that are used consist of managerial ownership, institutional ownership, independent commissioners, board of commissioners, and audit committees. Research using secondary data from 2010 – 2012 annual reports of various companies manufacturing industrial sectors and consumer goods contained in the Indonesia Stock Exchange (IDX). The sampling method used in this study was purposive sampling. The sample consists of 47 companies. The results show that the independent commissioners, board of commissioners, and financial distress condition have a significant effect on voluntary disclosure. While managerial ownership, institutional ownership, and audit committees does not significantly influence voluntary disclosure. Keywords: corporate governance, financial distress, voluntary disclosure.